In Vitro and In Silico Anthelmintic Activity of Extracts of Lannea kerstingii and Ficus thonningii on Heligmosomoides polygyrus - Ndjinkeu Ntcheuzing Serena; Masoud Besati; Noumedem Anangmo Christelle Nadia; Mahdi Yaghoobi; Yamssi Cédric; Claire Ciancia; Ngouyamsa Nsapkain Aboubakar Sidiki; Vincent Khan Payne; Mpoame Mbida; Haibo Hu (Journal of Parasitology Research)
Conclusion: The use of L. kerstingii and F. thonningii for the treatment of helminthiasis has been proved in vitro and in silico by this research. However, more research is required, especially on the acute toxicity and in vivo anthelmintic efficacy to validate this scientific investigation.